2013
DOI: 10.1002/prot.24472
|View full text |Cite
|
Sign up to set email alerts
|

Human interleukin‐23 receptor antagonists derived from an albumin‐binding domain scaffold inhibit IL‐23‐dependent ex vivo expansion of IL‐17‐producing T‐cells

Abstract: Engineered combinatorial libraries derived from small protein scaffolds represent a powerful tool for generating novel binders with high affinity, required specificity and designed inhibitory function. This work was aimed to generate a collection of recombinant binders of human interleukin-23 receptor (IL-23R), which is a key element of proinflammatory IL-23-mediated signaling. A library of variants derived from the three-helix bundle scaffold of the albumin-binding domain (ABD) of streptococcal protein G and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 41 publications
(59 reference statements)
0
47
0
1
Order By: Relevance
“…To the best of our knowledge, it is not known whether IL-12p35 needs p40 for interaction with IL-12R␤1 and IL-12R␤2, but binding of the other cytokine members of the IL-6/IL-12 type cytokine family to their ␤ receptors depends on the preceding complex formation with the ␣ receptor subunit (28 -30). Although, a recent report showed that bacterially expressed and refolded p19 is able to bind to IL-23R in the absence of p40 (31), this study lacks the general demonstration of the biological activity of bacterially produced p19 in complex with p40 and IL-23R/IL-12R␤1. As observed previously by Oppmann et al (8), secretion of p19 was promoted by p40 coexpression (Fig.…”
Section: Methodsmentioning
confidence: 70%
“…To the best of our knowledge, it is not known whether IL-12p35 needs p40 for interaction with IL-12R␤1 and IL-12R␤2, but binding of the other cytokine members of the IL-6/IL-12 type cytokine family to their ␤ receptors depends on the preceding complex formation with the ␣ receptor subunit (28 -30). Although, a recent report showed that bacterially expressed and refolded p19 is able to bind to IL-23R in the absence of p40 (31), this study lacks the general demonstration of the biological activity of bacterially produced p19 in complex with p40 and IL-23R/IL-12R␤1. As observed previously by Oppmann et al (8), secretion of p19 was promoted by p40 coexpression (Fig.…”
Section: Methodsmentioning
confidence: 70%
“…In this work, we generated insoluble fibrin-targeted protein binders useful for development of thrombus imaging agents. For this non-immunoglobulin approach, combinatorial library derived from 5.5 kDa albumin-binding domain of streptococcal protein G was chosen as this library of theoretical complexity up to 10 14 protein variants has already provided binders of several important protein targets [31,34,41], some of them with nanomolar or even sub-nanomolar binding affinity [30,32,33]. To stabilize small protein binders, 305 amino acid helical TolA protein is being used to form 38 kDa fusion binding variants.…”
Section: Discussionmentioning
confidence: 99%
“…Combinatorial DNA library was generated as described previously [33,34] with some modifications. The assembled library was in vitro transcribed/translated in a single step reaction using E. coli extract (EasyXpress E. coli kit, biotechrabbit, Hennigsdorf, Germany) and used for the pre-selection in 96well Maxisorp plates (NUNC, Roskilde, Denmark).…”
Section: Ribosome Display Selection Of Bindersmentioning
confidence: 99%
“…TSA was performed with the real-time PCR Detection System CFX touch (BIO-Rad Laboratories, Hercules, USA) according to [12]. The data were analyzed with CFX Manager Software and the melting temperatures (Tm) determined using the first derivative spectra.…”
Section: Methodsmentioning
confidence: 99%